2009
DOI: 10.1002/jhm.386
|View full text |Cite
|
Sign up to set email alerts
|

A hospitalist‐run short‐stay unit: Features that predict length‐of‐stay and eventual admission to traditional inpatient services

Abstract: BACKGROUND: Short‐stay units (SSUs) provide an alternative to traditional inpatient services for patients with short anticipated hospital stays. Yet little is known about which patient types predict SSU success. OBJECTIVE: To describe patients admitted to our hospitalist‐run SSU and explore predictors of length‐of‐stay (LOS) and eventual admission to traditional inpatient services. DESIGN: Prospective observational cohort study. SETTING: Large public teaching hospital. PATIENTS: Consecutive admissions (n = 755… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 12 publications
1
28
1
2
Order By: Relevance
“…Data were collected on 14 different variables that might have affected length of stay. Some variables have previously been shown to predict a 'failed' short stay, that is, admission for >72 h. These include: inability to independently mobilise, ongoing active treatment, need for specialty consultation, requirement of multidisciplinary assessment, inaccessibility of diagnostic tests, weekend admissions and transfer to intensive care units 4,10,11 . Increasing age has been shown by some to be associated with increased length of stay 4 but not others.…”
Section: Study Limitations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were collected on 14 different variables that might have affected length of stay. Some variables have previously been shown to predict a 'failed' short stay, that is, admission for >72 h. These include: inability to independently mobilise, ongoing active treatment, need for specialty consultation, requirement of multidisciplinary assessment, inaccessibility of diagnostic tests, weekend admissions and transfer to intensive care units 4,10,11 . Increasing age has been shown by some to be associated with increased length of stay 4 but not others.…”
Section: Study Limitations and Discussionmentioning
confidence: 99%
“…Data were collected on 14 different variables (Table 1) using a data collection proforma. These variables were chosen because they had either previously been shown to affect length of stay 4,7,10,11 or were thought to be relevant after discussion with the multidisciplinary team.…”
Section: Methodsmentioning
confidence: 99%
“…35 Historically, SSU have been under the domain of the ED; however, there is an emerging role for hospitalistrun SSU. 36 Despite demand for SSU, little research has been performed on hospitalist-led SSU. In 2000, Abenhaim and colleagues showed that a hospitalist-run SSU at a university-affiliated teaching hospital had a shorter LOS and lower rates of complications and readmissions when compared to medicine teaching services.…”
Section: Short Stay Unitsmentioning
confidence: 99%
“…Lucas and colleagues found that whether or not SSU patients required assistance of specialists was the strongest predictor of unsuccessful stays (>72 hours or inpatient conversion) in SSU. 36 Whether SSU are run by hospital medicine or emergency medicine is decided at an institutional level. Location of SSU in a specifically designated area is crucial, as it allows physicians to round efficiently on patients and to work with staff trained in observation services.…”
Section: Short Stay Unitsmentioning
confidence: 99%
“…There are only a few medical SSU reports in other countries, namely United States (US), United Kingdom (UK) and Canada [1][2][3]. SSU descriptions have also been reported for groups of patients with specific diagnoses such as asthma, head injuries or chest pain [4][5][6].…”
Section: Introductionmentioning
confidence: 98%